Informality, Food Insecurity and Intra-Household Resource Allocation: Evidence from Pakistan - Sultana, Shagufta (iRASD Journal of Economics, 2023)
The significance of employment in alleviating household poverty and enhancing overall well-being is widely acknowledged. In Pakistan, even with the notable growth in agricultural production, the country struggles with significant levels of food insecurity, affecting approximately 20.3 percent of the population, as indicated by a 2019 global report. This research investigates the impact of informal employment on the Food Insecurity Experience Scale (FIES) and the distribution of resources within households, including categories such as food, non-food items, education, and health. Utilizing data from the Household Integrated Economic Survey (HIES) conducted in 2018-19, fractional response and ordered logit models were employed to analyze the influence of informal employment on resource allocation across various categories and household food insecurity. The findings indicated that households headed by individuals in informal employment typically allocate a more significant portion of their budget to food and health than those in formal employment. Moreover, the impact of informal employment on non-food expenses appears limited, and households with informal workers demonstrate reduced spending on education compared to their formal counterparts. Additionally, the study highlights a higher probability of severe or moderate food insecurity levels in households headed by individuals in informal employment. Comprehending employment and household welfare dynamics necessitates a thorough understanding of intra-household dynamics. This research contributes valuable insights for policymakers, aiding in identifying critical areas for expanding social protection measures for informal workers.